1979
DOI: 10.1093/nar/6.7.2637
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the RNA and protein binding sites of the E.coli ribosomal protein L10

Abstract: We have used modification of specific amino acid residues in the E. coli ribosomal protein L10 as a tool to study its interactions with another ribosomal protein, L7/L12, as well as with ribosomal core particles and with 23S RNA. The ribosome and RNA binding capability of L10 was found to be inhibited by modification of one more of its arginine residues. This treatment does not affect the ability of L10 to bind four molecules of L7/L12 in a L7/L12-L10 complex. Our results support the view that L10's role in pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
5

Year Published

1981
1981
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 23 publications
2
16
0
5
Order By: Relevance
“…The N Terminus of P0 Is Crucial for rRNA Binding-It has been reported that E. coli L10 and L10⅐L7/L12 complex bind directly to the 1070 region of 23 S rRNA (3,38,39), and the L10 fragment lacking the N-terminal 1-69 amino acids fails to assemble into the ribosome, together with L7/L12 (35). In eukaryotes, the yeast P0 variant lacking the C-terminal 87 residues can assemble into the ribosome in vivo with weakly bound P1/P2 (25).…”
Section: Discussionmentioning
confidence: 99%
“…The N Terminus of P0 Is Crucial for rRNA Binding-It has been reported that E. coli L10 and L10⅐L7/L12 complex bind directly to the 1070 region of 23 S rRNA (3,38,39), and the L10 fragment lacking the N-terminal 1-69 amino acids fails to assemble into the ribosome, together with L7/L12 (35). In eukaryotes, the yeast P0 variant lacking the C-terminal 87 residues can assemble into the ribosome in vivo with weakly bound P1/P2 (25).…”
Section: Discussionmentioning
confidence: 99%
“…This is comparable with the fact that rat L12 and anti-28 S recognize a similar tertiary structure of the eukaryotic GTPase domain. The E. coli-L8 complex (a counterpart of the rat P complex) binds to the GTPase domain of 23 S rRNA through L10 moiety (Pettersson et al, 1976;Pettersson, 1979;Beauclerk et al, 1984) and protects mainly the internal loop region comprising residues 1044 -1050 and 1109 -1111 against chemical reagents and nuclease (Egebjerg et al, 1990;Rosendahl and Douthwaite, 1993). This loop region is highly conserved; 7 of 10 bases are preserved between E. coli and rat.…”
Section: Conserved Protein Binding Features Of the Gtpase Domain-mentioning
confidence: 99%
“…This raised the questions of whether stoichiometries other than 4:1 and 6:1 exist in bacteria, whether a given stoichiometry is related to a particular taxonomic group or a specific living environment, or which evolutionary processes resulted in a given stoichiometry. Biochemical and mass spectrometry methods that were used so far to quantify the L12 copy numbers 9,[17][18][19][20]21,23 are not suitable for a large-scale screening of hundreds of species. Here we used computational tools to predict the ribosomal L12 stalk composition for a wide range of bacteria, mitochondria and chloroplasts.…”
mentioning
confidence: 99%